New Nest (Manila Bulletin, 2018)
Regine Velasquez is officially declared Kapamilya and she's buckling down to work where she belongs. Regine Velasquez-Alcasid will continue to be everywhere, anytime even on the other side of the fence. For more details visit us at UP College of Music Library.